Lafẓu al Ibtahālāti qabla Khuṭbati al Jum’ati fī al Masājidi Madīnati Jāmbi (Dirāsatun fī ‘Ilmi al Aṣwāti) - Khairan, Ahmad; Mahendra, Ahdiyat (Al-Uslub: Journal of Arabic Linguistic and Literature, 2020)
This study analyzes lafaz Ibtihalat reviewed from Ashwat Science. Lafaz Ibtihalat is a prayer that is read before Friday prayers. This study was conducted because researchers found the problem of pronunciation at ibtihalat mosque jambi city, especially in the pronunciation of prayer before Friday Khutbah. The type of research used is qualitative research. The purpose of this research is :1. Seeing ibtihalat pronunciation mistakes that often occur as common as Friday sermons. 2. Correcting ibtihalat reading error before Friday Sermon The results of this study are 1. In this study phonological errors were found in the form of mismatch of makhraj letters resulting in the conversion of one letter to another. The accuracy of pronunciation in a speech is important because it can affect the meaning referred to by the speaker. Among these errors, the most errors are in the pronunciation of the letters س" "and" " ا As well as the pronunciation error On lafaz معاندa الدين which reads معان الديهم . 2. Correct the error of the Pronunciation of ibtihalat before Khutbah by analyzing each letter and looking at the difference between the correct lafaz and the wrong lafaz by using the analysis of Kitabatul Ashwat on lafaz ibtihalat before friday's sermon in accordance with the rules of Aswat Science